2005
DOI: 10.1155/2005/565479
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gemcitabine in the Treatment of Cholangiocarcinoma and Gallbladder Cancer: A Systematic Review

Abstract: In appropriate patients with gallbladder cancer or cholangiocarcinoma, surgery offers the best chance for survival and should remain the first treatment of choice. For patients not considered candidates for surgery, but willing and able to tolerate chemotherapy alone or in combination with a fluoropyrimidine (such as 5-fluorouracil or capecitabine), gemcitabine appears to be a reasonable alternative to best supportive care, although this conclusion has not been confirmed with a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 11 publications
2
29
0
1
Order By: Relevance
“…However, combination chemotherapy resulted in a marginally better response rate (CR þ PR: 27.8 vs 22.6%), and superior tumour control rate (CR þ PR þ SD: 75.0 vs 58.0%), broadly in line with that seen in previous studies (Dingle et al, 2005). Both treatment arms were well tolerated, although patients who received doublet therapy showed a significant increase in lethargy (28.6 vs 9.1%); the effect of this finding on the quality of life was not explored in this study.…”
Section: Discussionsupporting
confidence: 89%
“…However, combination chemotherapy resulted in a marginally better response rate (CR þ PR: 27.8 vs 22.6%), and superior tumour control rate (CR þ PR þ SD: 75.0 vs 58.0%), broadly in line with that seen in previous studies (Dingle et al, 2005). Both treatment arms were well tolerated, although patients who received doublet therapy showed a significant increase in lethargy (28.6 vs 9.1%); the effect of this finding on the quality of life was not explored in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Gemcitabine (GEM), which is phosphorylated by deoxycytidine kinase to interfere DNA synthesis after endocytosis[144, 145], is frequently used as the first-line therapy in clinical treatment for pancreatic cancer. However, the rapid emergence of drug resistance significantly limited the application of GEM.…”
Section: Mechanism Underlying Combination Chemotherapymentioning
confidence: 99%
“…A systemic review of 13 single-arm phase II trials confirmed the benefits of gemcitabine in combination with a fluoropyrimidine (5-FU or capecitabine) for ABC (20). We have previously reported that gem-cap is beneficial for ABC with an overall response rate of 58%, a PFS of 9.0 mo and median OS of 14 mo (12).…”
Section: Discussionmentioning
confidence: 92%